The journal „Mūsų žinynas“ about applications of mathematics in military topography in 1922-1940: authors and their articles - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2011)
Just after the end of the struggles for consolidation of the Independence, Lithuanian Army began care about development of military science. In addition to other sciences, a great attention was paid to applications of mathematics in military arts. In 1922-1940, journal of military science and history “Mūsų žinynas” (“Our Directory”) published 87 articles about various applications of mathematics in the Army. They included 27 articles on application of mathematics in military topography. The articles were written by 14 known and 1 unknown authors. 14 known authors included 12 army officers and 2 civilians.